1998
DOI: 10.1051/agro:19980703
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Granier's sap flux sensor in young mango trees

Abstract: -Granier's technique of measuring sap flux density using a continuous heating system was tested on young mango trees. On containerized trees, sap flow underestimated transpiration measured gravimetrically by less than 10 %. In a 4-year-old field-grown tree, there was only a 5 % difference between cumulative summed sap flow in the branches and sap flow in the trunk over a 24-h period. Positioning of the sap flux sensor on the trunk was found to be non-critical for sap flow measurement in trees of diameter of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 13 publications
0
19
0
3
Order By: Relevance
“…Few laboratory tests have been performed between measured sapflow and gravimetric measurements of water loss. A cut-tree comparison on grapevine (Vitis vinifera L.) [2] and a lysimeter study on mango (Mangifera indica L.) [29] showed good agreement with the original calibration at flow rates up to 225 g m -2 s -1 . Clearwater et al [13] found that heat dissipation probes used with the original Granier calibration underestimated water flow through excised stems from several species if the probe was in partial contact with non-active xylem.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Few laboratory tests have been performed between measured sapflow and gravimetric measurements of water loss. A cut-tree comparison on grapevine (Vitis vinifera L.) [2] and a lysimeter study on mango (Mangifera indica L.) [29] showed good agreement with the original calibration at flow rates up to 225 g m -2 s -1 . Clearwater et al [13] found that heat dissipation probes used with the original Granier calibration underestimated water flow through excised stems from several species if the probe was in partial contact with non-active xylem.…”
Section: Introductionmentioning
confidence: 92%
“…Our studies, as well as others, suggest that the Granier system loses sensitivity at higher flow rates. However, it has been shown that the original calibration is valid even for high flow densities in grape vines (225 g m -2 s -1 ) [2] and in mango (120 g m -2 s -1 ) [29]. The original calibration does not show any large errors up to 150 g m -2 s -1 [17,18].…”
Section: Comparison Of the Two Systemsmentioning
confidence: 99%
“…This resulted in an overall 54% error in SFD (i.e., approximately 1.5 times the sap flux density calculated from Equation (1)). Using the same method, Lu and Chacko [38] found that the TDP method underestimated cumulative daily SFD by 6-10% in two Mangifera indica trees. Steppe et al [33] found an underestimate of SFD by 60% in Fagus grandifolia trees.…”
Section: Calibration Of Parameters For the Original Granier Equationmentioning
confidence: 98%
“…No caso da cultura da manga, alguns estudos envolvendo os métodos térmicos para a quantificação do fluxo de seiva foram realizados (Lu & Chacko, 1998;Coelho Filho et al, 2006) e evidenciaram bons resultados de estimativas do fluxo de seiva comparadas a transpiração medidas em lisímetros. Coelho Filho et al (2006), trabalhando com lisímetros de pesagem, encontraram boa resposta dinâmica do MDT e subestimativas que devem ser corrigidas a fim de se quantificar a transpiração.…”
Section: Introductionunclassified